The Effect of Using E-Learning Environments on Teaching Computer Material to Develop the Knowledge Needs of The Second Secondary Students in Jordan - AlArood, Khaled Ibrahim Mohammad (Journal of Educational and Psychological Sciences, 2020)
This research aims to know the Effect Of Using E-Learning Environments On Teaching Computer Material To Develop The Knowledge Needs Of The Second Secondary Students In Jordan, In Ajloun Governorate, an e-learning environment was designed to teach the unit of counting from computer material to them, and a pre-application was conducted for research tools (cognitive achievement test) and then experimental treatment, then a post-application application of the research tool (cognitive achievement test), and then the application of other treatment methods The appropriate environment using the SPSS program, and the researcher found that there is a statistically significant difference between the average scores of the research sample in the pre and post application of the cognitive achievement test for students in favor of the post application, and this indicates that the use of electronic learning environments has had a significant and effective impact in the development of the cognitive aspect Among students (the research sample), the research has recommended the need to take care of electronic learning environments and expand their use in the educational process in order to improve the knowledge level of students, in addition to the need to convert as many traditional courses as possible into electronic courses and contain them in environments Science encourages students to learn, and work to involve teachers in the management of e-learning environments in order to enable him to communicate with his students are always so as to achieve the desired educational goals.